Pelatihan Pembuatan Biochar Untuk Memperbaiki Kualitas Tanah di Desa Sinar Mulya Kabupaten Kaur - I Nyoman Candra; Elvinawati (Universitas Bengkulu, 2023)
[Biochar production practice to improve soil quality at Sinar Mulya Village, Kaur Regency] Sinar Mulya Village is belong to Kaur Regency territory whose population is working mostly as a plantation worker. Land management was conducted tradisionally resulting in wide land degradation. Moreover, the application of fertilizer is ineffective because water washes it away. The objective of this program is to deliver knowledge and skills for plantation workers at Sinar Mulya Village on how to produce biochar. This program started by inviting the participants . It was then followed by preparing the materials and place where the program took place on May 27, 2023. One day after, May 28, 2023, it was presented to the participants about what biochar is, and how biochar is produced. Presention and biochar practice section was attended by forty persons who joined in this program with strong motivation assessed from their participation and questionnaire falling in “Good” catagory. In general, this program run smoothly and gave a positive results.